Structure and properties of composite coatings prepared by electron beam melting with “titanium carbide - titanium binder”; Surface and Coatings Technology; Vol. 358 - Krinitsyn M. G. Maksim Germanovich; Pribytkov G. A. Gennady Andreevich; Korzhova V. V. Viktoriya Viktorovna; Firsina I. A. Irina Andreevna (2019, 2019)
Title screen